Diabetic Peripheral Neuropathy and its Risk Factors among Chronic Diabetic Patients in Southern Karnataka, India - Sneha Sri GR; Darshan BB; Aryan MG; Waseem Anjum; Damayanthi MN (Medsci Publications, 2024)
Background: The global prevalence of diabetes mellitus (DM) was 10.5% (2021). The common complications of DM include diabetic peripheral neuropathy (DPN) which affects 30% to 50% of diabetics. DPN is a debilitating complication of diabetes that significantly impairs the quality of life of individuals. Objectives: To estimate the magnitude of DPN using Michigan Neuropathy Screening Instrument (MNSI) and to determine the factors associated with it. Methodology: A facility based cross-sectional study was conducted among 100 participants with diabetes for more than 5years. Questionnaire included sociodemographic details, diabetes history, co-morbidities, personal habits, MNSI patient and clinical version for detecting DPN. Bivariate analysis was performed to determine the factors associated with DPN; multivariate analysis to determine the exact factors affecting DPN. Results: Proportion of DPN was 34% & 38% on MNSI interview and examination version respectively. Factors affecting DPN were age, tobacco consumption, age of diagnosis of DM, co-morbidities on bivariate analysis. Tobacco consumption [AOR- 6.72, CI-2.07-21.8, P=0.002] & co-morbidities [AOR- 7.19, CI-1.93-26.7, P=0.003] on multivariate analysis. Conclusion: Proportion of DPN remains high among individuals with diabetes. Smoking & presence of co-morbidities contributes to an increased risk of DPN.